Cameroon Budget Transparency Initiative : Lessons Learned and Recommendations for Local Councils - Agarwal, Sanjay; Alton, Martin Luis; Bove, Abel; Ngounoue, Victoire; Perrot, Vincent (World Bank, Washington, DC, 2014)
From 2011 to 2013, the World Bank-financed Budget Transparency Initiative1 has conducted a number of activities in the North-West and Adamawa Regions to make local council budgets more transparent and accessible to citizens. The pilot project developed and tested a number of tools and activities to increase the budget transparency of local councils and, in the process, to learn lessons about their efficacy. Based on the lessons learned dur¬ing the implementation of the pilot, this brief summarizes recommendations that are relevant to policy makers interested in scaling up efforts at increasing budget transparency at the local level.